LESSON FROM SOMALIA: A SPECIAL MODEL OF HANDLING PIRACY JURE GENTIUM AND ARMED ROBBERY AT SEA - Bunga, Gerald Aldytia (Faculty of Law, Parahyangan Catholic University, 2019)
In this article, the author discusses the issues pertaining to piracy jure gentium and armed robbery at sea. Focus shall be given on the incidence of both crimes occurring offshore Somalia during a certain time period. It is noted that Somalia is unable or unwilling to enforce its law to protect international (commercial) shipping passing through its waters. This inability to enforce the law has been the primary reason, Somalia was forced to seek legal assistance from the international community. By taking lessons from Somalia and comparing these two crimes, the author seeks to propose a model of how to tackle the problem at hand. To be discussed and analysed is a number of United Nations Security Council Resolutions which provide the international community with a guideline how to handle both crimes.